PARTISIPASI BELAJAR MAHASISWA DALAM PEMBELAJARAN BERBASIS ANDRAGOGI - Sayidiman Sayidiman; Asraruddin Lambogo (Publikasi Pendidikan, 2016)
This study reviews the level of student participation in the learning based on the concept of andragogy as preliminary studies for the research further. This study aims to determine the extent of student participation in the learning based on the concept of andragogy, further research is expected dapata benefit both theoretically and practically. research subjects are students Upp PGSD Parepare FIP UNM force in 2014 as the population. Research done by using survey techniques, data collection techniques used questionnaires to determine the general view mahasiswasiswa against the concept of learning Andragogy applied, the observation is made to collect data about the level of participation mahasiswasiswa in the learning process by applying the learning model based on the concept of andragogy, the study of documents used to collect data on student attendance in a presentation based learning Andragogy. Data were analyzed using quantitative descriptive analysis presented in the form of percentages and tables as explanatory exposure data.Keywords: andragogy learning, learning music